ENHANCING ORGANIZATIONAL AND LEGAL SUPPORT IN CONTEMPORARY COUNTERTERRORISM EFFORTS - Markieieva, Oksana; Rozvadovskyi, Bronislav (Стратегічна панорама, 2024)
The article draws on the previous research and delves into the nuances of the organizational and legal support of countering terrorism as a component of the national security system in Ukraine. With a focus on contemporary challenges, the article aims to clarify the current state of organizational and legal support for countering terrorism and to offer actionable proposals for its improvement. Terrorism in Ukraine presents a complex and precarious situation, with Russia serving as the primary external catalyst of these threats. Through multifaceted strategies spanning political, military, energy, economic, information and other domains, Russia aims to internally and externally destabilize, weaken and dismantle Ukraine. Alongside military operations, the ongoing threat of terror persists in the form of subversive-terrorist and other subversive activities conducted by Russian special services. Leverage a diverse array of techniques and resources, these services demonstrate considerable expertise and virtually unlimited material capabilities. The escalating terrorist threats in Ukraine demand a swift and robust response from the government, with a primary focus on establishing an effective regulatory and legal framework. The current insufficiency in regulating national legislation concerning counterterrorism, coupled with inconsistencies with the norms of international law, fosters an environment conducive to terrorism. Addressing these challenges requires enhancing the legal framework for combating terrorism, aligning legal regulation with the norms of international law, and executing the tasks related to the implementation of national security priorities provided for by the National Security Strategy of Ukraine "Human Security – Country Security" [1]. The research findings necessitate revisions to our special legislation on combating terrorism, harmonizing them with international legal documents ratified by our state. We formulate proposals to enhance the organizational and legal framework for entities engaged in counterterrorism efforts. These involve the development of counterterrorism security protocols, the further refinement of counterterrorism legislation, considering both current and potential terrorist threats to national security, as well as strengthening the effectiveness of countering terrorism financing in Ukraine and enhancing the system for combating cyber terrorism.